Implementasi Sanksi administrasi kepada wajib pajak bumi dan bangunan perdesaan dan perkotaan - Sakina Wardani Syamsir; Imron Burhan; Sri Nirmala Sari (Income Journal: Accounting, Management and Economic Research, 2022)
This research aims to give an overview of the administrative applying process to taxpayers who are late on paying land and buildings tax. This research used qualitative method with interview and documentation. The researc based in Undang-Undang No. 01 2013 about land and building tax, rural, city and operational standar procedure for collection of land and building tax, rual, city in Maros. The results of this research is implementation of administrative sanctionsis still lacking than it’s application, because Regional institution of finance does not follow up the late payment of land and building tax, rural, city, who have received the notice of tax due. The regional institution of finance in Maros is only wait for the consciousness of the tax payers to pay the tax, which is still payable